Simple and Versatile Molecular Donors for Organic Photovoltaics Prepared by Metal‐Free Synthesis. Issue 4 (27th November 2014) - Diac, Andreea; Demeter, Dora; Allain, Magali; Grosu, Ion; Roncali, Jean
Abstract Donor–acceptor molecules (D‐π‐A) built by connecting a diphenylhydrazone block to a dicyanovinyl acceptor group via various thiophene‐based π‐conjugating spacers (1–5) were synthesized from mono‐ or dialdehydes by a simple metal‐free procedure. Cyclic voltammetry and UV/Vis absorption spectroscopy show that the extension and/or increase of the donor strength of the spacer produces a decrease of the HOMO and LUMO energy level, a red shift of the absorption spectrum and an increase of the molecular absorption coefficient. Compared to solutions, the optical spectra of spin‐cast thin films of compounds 1–3 show a broadening and red shift of the absorption bands, consistent with the formation of J‐aggregates. In contrast the blue shift observed for the EDOT‐containing compounds 4 and 5 suggests the presence of H‐aggregates. Solution‐cast and vacuum‐deposited films of donors 1–5 were evaluated in solar cells with fullerene C60 as acceptor. A power‐conversion efficiency among the highest reported for bilayer devices of basic configuration was obtained with compound 2. On the other hand, the results obtained with 4 and 5 suggest that the presence of EDOT in the structure can have deleterious effects on the organization and performances of the donor material.